The EU in the Horn of Africa: Building Resilience as a Distant Form of Governance. (23rd October 2013) - Joseph, Jonathan
Abstract: The EU has recently got involved in resilience building. This article concentrates on the SHARE project relating to resilience building in the Horn of Africa. It suggests that resilience is best understood as part of a particular approach to governance. By employing the concept of governmentality it is suggested that the resilience project is part of a broader strategy that seeks to govern from a distance. It is argued that this is consistent with two other developments. First it fits with new approaches to development and global governance, something that is shown through a comparison with the work of USAID. And it fits with the EU's own internal processes both in the field of risk and disaster preparedness, and in relation to things like the open method of co‐ordination. Resilience has emerged as an important new approach and this will be at the heart of internal and external EU relations.